2021
DOI: 10.3389/fphar.2020.590457
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Pharmacology-Based Pattern to Uncover the Pharmacological Mechanism of Ginsenoside H Dripping Pills in the Treatment of Depression

Abstract: Objectives: To evaluate the pharmacodynamical effects and pharmacological mechanism of Ginsenoside H dripping pills (GH) in chronic unpredictable mild stress (CUMS) model rats.Methods: First, the CUMS-induced rat model was established to assess the anti-depressant effects of GH (28, 56, and 112 mg/kg) by the changes of the behavioral indexes (sucrose preference, crossing score, rearing score) and biochemical indexes (serotonin, dopamine, norepinephrine) in Hippocampus. Then, the components of GH were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…mediating the potential improvements of ginsenoside Rg1 in this CUMS-induced depression model Zhao et al (Zhao et al, 2020). adopted pharmacodynamics-network pharmacology mechanism verification found that ginsenoside H dripping pills significantly upregulated PKA activity and cAMP content in the hippocampus of CUMS model rats.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…mediating the potential improvements of ginsenoside Rg1 in this CUMS-induced depression model Zhao et al (Zhao et al, 2020). adopted pharmacodynamics-network pharmacology mechanism verification found that ginsenoside H dripping pills significantly upregulated PKA activity and cAMP content in the hippocampus of CUMS model rats.…”
mentioning
confidence: 85%
“…Thus, it appears that the ERK‐CREB‐BDNF signaling pathway within the PFC may be critically involved in mediating the potential improvements of ginsenoside Rg1 in this CUMS‐induced depression model. Zhao et al (Zhao et al, 2020) adopted pharmacodynamics‐network pharmacology mechanism verification found that ginsenoside H dripping pills significantly upregulated PKA activity and cAMP content in the hippocampus of CUMS model rats. Therefore, ginsenoside H dripping pills may exert anti‐depressant effects by regulating cAMP‐PKA‐CREB‐BDNF signaling transduction.…”
Section: Pharmacological Actionsmentioning
confidence: 99%
“…For instance, ultra-performance liquid chromatography-quadrupole-time-of-flight mass spectrometry (UPLC-Q-TOF-MS) was used for the chemical profiling of Isatis indigotica roots and leaves, and the active constituents present in I. indigotica were then screened using the prediction of gastrointestinal absorption and drug-likeness (DL) analysis in SwissADME (http://www.swissadme.ch) [9] . The active components in ginsenoside H dripping pills were identified by UPLC-Q-TOF-MS and then filtered based on oral bioavailability (OB) and DL [10] . To detect the volatile compounds from Scutellaria baicalensis , gas chromatography-MS (GC-MS) was performed.…”
Section: Network Pharmacology For Chm Researchmentioning
confidence: 99%
“…The chief target proteins cAMP, PKA, CREB, p-CREB, and BDNF were verified in CUMS model rats in cAMP signaling pathway. It was found that GH can activate cAMP-PKA-CREB-BDNF signaling pathway ( Zhao et al, 2020 ).…”
Section: Antidepressant Active Ingredients From Panax Notog...mentioning
confidence: 99%